Enhancing Switchgrass Growth With Biochar Derived From Mushroom Residue: A Study on Regulating Physicochemical Properties of Acidic Phosphogypsum - Xiang, Yangzhou; Mao, Yanting; Liu, Ying; Luo, Yang; Xue, Jianming; He, Ji; Shurpali, Narasinha J.; Bhattarai, Hem Raj; Deepagoda, T. K. K. Chamindu; Yao, Bin; Siddique, Kadambot H. M.; Li, Yuan (Wiley-Blackwell, 2025)
Acidity limits plant growth, particularly when the growing medium has a pH below 5, a challenge that is particularly relevant for certain plants like switchgrass (Panicum virgatum). Although adding biochar to the growing medium has been shown to improve plant growth by modulating acidity, its specific impact on switchgrass remains largely uninvestigated. Thus, we conducted a pot experiment to assess how different biochar application rates (0%, 1%, 2.5%, 5%, 10%, and 20% w/w), derived from mushroom residue through muffle furnace pyrolysis at 350°C for 2 h, affect the physicochemical attributes of phosphogypsum and subsequent switchgrass growth. Our findings revealed that adding biochar to phosphogypsum significantly alleviated acidity and enhanced moisture, organic matter, total nitrogen, total phosphorus, total potassium, available phosphorus, and available potassium contents. Notably, the 10% biochar treatment had the most positive impacts on germination rates, while the 5% treatment had the greatest improvements in shoot length, tiller number, and total weight compared to the control. Structural equation modeling illustrated that biochar indirectly contributed to switchgrass health by altering the physicochemical properties of phosphogypsum, with pH as the pivotal regulator. Our study demonstrated the potential of mushroom residue biochar as an effective amendment for acidic substrates/matrix (e.g., soil), offering a promising strategy to improve physicochemical conditions and stimulate plant growth.
Keywords: ameliorant effect; biochar; mushroom residue; phosphogypsum; switchgrass